Leptin 2014
DOI: 10.1007/978-3-319-09915-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Hepatic Steatosis and Fibrosis: Role of Leptin

Abstract: Nonalcoholic fatty liver disease (NAFLD) encompasses a spectrum of liver abnormalities, ranging from simple steatosis, to steatohepatitis and cirrhosis, in the absence of "excessive" alcohol consumption or any other identifi able cause(s) for liver disease [ 1 ]. Histologically, NAFLD can be categorized into: (1) simple steatosis in the absence of hepatocellular injury (nonalcoholic fatty liver, NAFL); and (2) steatohepatitis (nonalcoholic steatohepatitis, NASH), characterized by the presence of steatosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 147 publications
0
9
0
Order By: Relevance
“…-S61- [17] . As a result of synergistic action of other adipocytokines such as tumor necrosis factor (TNF-α ) , fatty liver may progress to steatohepatitis by lipoapoptosis induction , which leads to the recruitment of inflammatory cells , contributing to its progression and subsequently causing hepatocellular damage , such as cell swelling and appearance of Mallory bodies (Magkos F) [18] .Leptin has proven to be important in the progression of hepatic steatosis (Magkos F) [19] . Our study showed significantly higher ascitic fluid leptin level compared to serum in our patient in both group I, II .…”
Section: Discussionmentioning
confidence: 99%
“…-S61- [17] . As a result of synergistic action of other adipocytokines such as tumor necrosis factor (TNF-α ) , fatty liver may progress to steatohepatitis by lipoapoptosis induction , which leads to the recruitment of inflammatory cells , contributing to its progression and subsequently causing hepatocellular damage , such as cell swelling and appearance of Mallory bodies (Magkos F) [18] .Leptin has proven to be important in the progression of hepatic steatosis (Magkos F) [19] . Our study showed significantly higher ascitic fluid leptin level compared to serum in our patient in both group I, II .…”
Section: Discussionmentioning
confidence: 99%
“…These factors include genetic, environmental and psychological conditions. Abdominal obesity (central obesity) is strongly related to Non-Alcoholic Fatty Liver Disease (NAFLD) and Insulin Resistance (IR), mainly because of the excessive body fat in the central region [5,17,25 ] . These conditions lead to a series of complications due to systemic arterial hypertension, dyslipidemia, and inflammation, which are present in metabolic syndrome (MS).…”
Section: Obesity and Inflammationmentioning
confidence: 99%
“…Two sequential events act as important mechanisms in the establishment and progression of hepatic steatosis: i) continual fatty acids accumulation in hepatocytes and ii) increase of hepatic oxidative stress [56]. The action of oxidative stress is due to the overload of accumulated liver lipids, resulting in oxidation of these compounds of fatty acids and release of lipid peroxides that produce reactive oxygen species (ROS) [12,25].…”
Section: Leptin and Hepatic Steatosismentioning
confidence: 99%
See 2 more Smart Citations